2008
DOI: 10.1002/ejic.200800200
|View full text |Cite
|
Sign up to set email alerts
|

The Fabrication and Magnetic Properties of Ni Fibers Synthesized Under External Magnetic Fields

Abstract: One-dimensional (1D) nanocrystallites Ni fibers with different lengths were fabricated by the reduction of Ni 2+ ions by hydrazine hydrate in the presence of external magnetic fields. The effect of the reaction conditions and magnetic field intensity on the microstructures and magnetic properties of the Ni fibers were systematically investigated by scanning electron microscopy (SEM), X-ray diffraction (XRD), and measurement of hysteresis loops at room temperature. It was found that both the intensity of the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…It is also worth mentioning here that it is possible to synthesize single crystalline nanostructures using template method by proper and tight control of the process parameters [23]. There also have been attempts to improve and obtain highly aligned 1D nanostructures by applying external magnetic field during the synthesis [24,25]. To date, many synthesis and characterization methods have been developed and employed to help us synthesize and characterize 1D nanostructures, but due to the nature of the formed nanostructures which exhibit different behavior at different conditions (environmental and synthesis), a full knowledge of these 1D nanostructures and the influence of synthesis parameters are still in their early stages.…”
Section: Introductionmentioning
confidence: 99%
“…It is also worth mentioning here that it is possible to synthesize single crystalline nanostructures using template method by proper and tight control of the process parameters [23]. There also have been attempts to improve and obtain highly aligned 1D nanostructures by applying external magnetic field during the synthesis [24,25]. To date, many synthesis and characterization methods have been developed and employed to help us synthesize and characterize 1D nanostructures, but due to the nature of the formed nanostructures which exhibit different behavior at different conditions (environmental and synthesis), a full knowledge of these 1D nanostructures and the influence of synthesis parameters are still in their early stages.…”
Section: Introductionmentioning
confidence: 99%
“…In order to control the properties of the electrodeposit, it is important to understand the effect of external magnetic field during the electrochemical processes. In previous works, external magnetic fields have been applied during the synthesis process to control structural and magnetic properties of 1D nanostructures [21,22]. It has been observed that external magnetic field can induce changes in surface morphology and preferential growth direction in case of Ni or Ni-Fe grains [21,27].…”
Section: Introductionmentioning
confidence: 99%
“…To date, a number of synthesis and characterization methods have been employed to study Ni nanowires. Specifically, the effect of electrodeposition process parameters such as solution pH, bath temperatures, current and additives on the growth and morphology of the Ni nanowires has been investigated [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The above research mainly focused on the hydrothermal or chemical reduction method to prepare nickel materials. In addition, magnetic‐field‐induced assembly method was also widely applied in the synthesis of variously shaped nickel crystals . For example, 1D nickel wires were obtained via the magnetic‐field‐dependent synthesis .…”
Section: Introductionmentioning
confidence: 99%
“…For example, 1D nickel wires were obtained via the magnetic‐field‐dependent synthesis . The preparation of nickel materials with other morphologies (such as Ni fibers) was also reported . The above referred synthesis of nickel crystal was almost performed at above RT by the aid of heating, which was in the need of energy consumption.…”
Section: Introductionmentioning
confidence: 99%